Interoperable information model for geovisualization and interaction in XR environments. Issue 7 (2nd July 2020) - Seo, Daeil; Yoo, Byounghyun
ABSTRACT: Since the vision of a Digital Earth (DE) was introduced in 1998, geo-browsers seem to have nearly fulfilled this vision. Virtual reality (VR) for visualizing the DE provides an immersive user experience in a mirror world. Location-based augmented reality (AR) browsers have been introduced and provide content according to user and environmental contexts. However, the content models of traditional geo-browsers and AR browsers have very limited interoperability, because they are described in application-specific formats using their domain standards. Each application is vertically integrated from content to application. The Web is an interoperable and open platform, and hundreds of millions of users are already using it to create and share content. To envision DE browsers for cross-reality (XR) environments that concurrently support geovisualization as well as VR, AR, and mixed-reality environments, we propose a DE content model based on Web standards and architecture that provides full interoperability and openness for XR browsers as a first-class citizen of the Web. This is expected to improve the DE content development efficiency by fully using the Web content development environment.